Pancreatic Enucleation Patients Share the Same Quality of Life as the General Population at Long-Term Follow-Up: A Propensity Score-Matched Analysis - Giuliani, Tommaso; De Pastena, Matteo; Paiella, Salvatore; Marchegiani, Giovanni; Landoni, Luca; Festini, Michele; Ramera, Marco; Marinelli, Veronica; Casetti, Luca; Esposito, Alessandro; Bassi, Claudio; Salvia, Roberto (Annals of surgery, 2023)
The aim of this study was to assess short- and long-term outcomes including quality of life (QoL) following pancreatic enucleation (PE). PE is deemed to preserve both the endocrine and the exocrine function while ensuring radicality. However, to assess whether this reflects an actual benefit perceived by patients, QoL has to be considered. Data from all consecutive patients undergoing PE from January 2010 to December 2019 were retrospectively analyzed. Surgical outcomes were graded according to the Clavien-Dindo classification, and EORTC-C30 and the EORTC-Pan26 were administered as a cross-sectional assessment of QoL. A control group consisting of healthy individuals from the general population was obtained and matched using the propensity score matching method. Eighty-one patients underwent PE using the open (59.3%), laparoscopic (27.2%), or robot-assisted (13.5%) approach. Sixty-five (80.2%) patients exhibited functioning/nonfunctioning pancreatic neuroendocrine tumors at final pathology.Surgical morbidity and complications of a Clavien-Dindo grade ≥3 were 48.1% and 16.0%, respectively. In-hospital mortality was 0%. Postoperative pancreatic fistula, post-pancreatectomy hemorrhage, and delayed gastric emptying rates were 21.0%, 9.9%, and 4.9%, respectively.Patients returned the questionnaires after a median of 74.2 months from the index surgery. Postoperative new onset of diabetes mellitus (NODM) was observed in 5 subjects (7.1%), with age being an independent predictor. Seven patients (10.0%) developed postoperative exocrine insufficiency. At the analysis of QoL, all function and symptom scales were comparable between the 2 groups, except for 2 of the EORTC-Pan 26 symptom scales, ("worries for the future" and "body image", P < 0.05). Despite being associated with significant postoperative morbidity, PE provides excellent long-term outcomes. The risk of NODM is low and related to patient age, with QoL being comparable to the general population. Such information should drive surgeons to pursue PE whenever properly indicated.